PENGARUH PENDAPATAN, PENGETAHUAN DAN LINGKUNGAN TERHADAP MOTIVASI MASYARAKAT DALAM MEMBAYAR ZAKAT MAL (STUDI KASUS DESA TELANG KARYA KECAMATAN MUARA TELANG): Pengaruh Pendapatan, Pengetahuan Dan Lingkungan Terhadap Motivasi Masyarakat Dalam Membayar Zakat Mal (Studi Kasus Desa Telang Karya Kecamatan Muara Telang). - Wakhid Sobirin, Muhammad; Hilda, Hilda; Rachmania, Rachmania (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2024)
Mal zakat can be used as a solution to overcome poverty that occurs in South Sumatra. However, until now the potential of mall zakat funds has not been maximally explored so that the function of mall zakat to overcome poverty has not been achieved. As a first step to increasing the collection of zakat funds, this research tries to identify variables that can influence people's motivation to pay zakat malls. Where the research location chosen was Telang Karya Village, Banyuasin Regency with a sample size of 97 respondents. This research examines the variables that influence the motivation of the people of Telang Karya Village in paying zakat mal by reducing the independent variables in the form of income, knowledge and environment. The survey results were analyzed using income distribution theory, science theory and social environmental theory. The purpose of this research is to find out whether the amount of income, knowledge and environment can influence a person's motivation to pay for the mall. The approach used is a quantitative descriptive approach. Based on the results of multiple regression analysis using the SPSS 23 program, it shows that the variables income, knowledge and environment have a positive and significant effect on the motivation of the people of Telang Karya Village in paying zakat mal.